2020
DOI: 10.1111/1365-2664.13724
|View full text |Cite
|
Sign up to set email alerts
|

Projected impacts of warming seas on commercially fished species at a biogeographic boundary of the European continental shelf

Abstract: 1. Projecting the future effects of climate change on marine fished populations can help prepare the fishing industry and management systems for resulting ecological, social and economic changes. Generating projections using multiple climate scenarios can provide valuable insights for fisheries stakeholders regarding uncertainty arising from future climate data. 2. Using a range of climate projections based on the Intergovernmental Panel on Climate Change A1B, RCP4.5 and RCP8.5 climate scenarios, we modelled a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Due to anthropogenic increases in CO 2 , the ocean is undergoing rapid changes resulting in increasing sea surface temperature among other stressors (Pörtner et al, 2019). Variations in temperature strongly impact fish biology through influencing growth, reproduction, and metabolism (Pörtner, 2002) where climate projections show species-specific increases and decreases in fish abundance (Wernberg et al, 2013(Wernberg et al, , 2016Maltby et al, 2020). In Hawai'i, increasing sea surface temperature has varying effects, where fish biomass increased for detritivores but decreased for browsers (Heenan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Due to anthropogenic increases in CO 2 , the ocean is undergoing rapid changes resulting in increasing sea surface temperature among other stressors (Pörtner et al, 2019). Variations in temperature strongly impact fish biology through influencing growth, reproduction, and metabolism (Pörtner, 2002) where climate projections show species-specific increases and decreases in fish abundance (Wernberg et al, 2013(Wernberg et al, , 2016Maltby et al, 2020). In Hawai'i, increasing sea surface temperature has varying effects, where fish biomass increased for detritivores but decreased for browsers (Heenan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…; Ofstad et al, 2013). This overlap in space, depth and time could have even been increased by recent changes of geographical and bathymetric distributions of both species, potentially as consequence of climate change (Maltby et al, 2020). According to mitochondrial DNA, which is maternally inherited in most animals (Moritz et al, 1987), we found that most hybrids (27 out of 30) resulted from a black anglerfish mother and a white anglerfish father.…”
Section: Discussionmentioning
confidence: 99%
“…There is also overlap in both species´ bathymetric distribution (20-1000m and 100-500m depth respectively for white and black anglerfish) (Azevedo, 1995;Caruso, 1986;García-Rodríguez, Pereda, Landa, & Esteban, 2005;Quincoces, Santurtún, & Lucio, 1998), and in spawning periods, both spawning in winter and spring (Ofstad, Angus, time could have even been increased by recent changes of geographical and bathymetric distributions of both species, potentially as a consequence of climate change (Maltby, Rutterford, Tinker, Genner, & Simpson, 2020). According to mitochondrial DNA, which is maternally inherited in most animals (Moritz, Dowling, & Brown, 1987), we found that most hybrids (27 out of 30) resulted from a black anglerfish mother and a white anglerfish father.…”
Section: Causes and Consequences Of Interspecific Hybridizationmentioning
confidence: 99%
“…Global warming is expected to have profound consequences on biodiversity and functioning of major systems on Earth 1 , 2 . The impact of temperature increase has been measured over the past two decades 3 6 , but understanding how this physical forcing affects ecosystems is unclear, particularly in the sea 7 9 . This, however, is critical for predicting the consequences of global warming and identifying mitigation and restoration actions.…”
Section: Introductionmentioning
confidence: 99%